A minority of athletes pass symmetry criteria in a series of hop and strength tests irrespective of having an ACL reconstructed knee or being noninjured - Markström, J. L.; Naili, J. E.; Häger, C. K. (Sports Health: A Multidisciplinary Approach, 2023)
Background: Between-leg symmetry in 1-leg hop and knee strength performances is considered important after anterior cruciate ligament reconstruction (ACLR) to facilitate a safer return to sport. While few athletes with ACLR demonstrate symmetry in test batteries, reference data for noninjured athletes are lacking, thus questioning how ACLR-specific poor symmetry is.